Alternative religion kids: spiritual and cultural identity among children and youth involved with new religious movements. Issue 1 (2nd January 2019) - Pratezina, Jessica
ABSTRACT: The term 'new religious movement' (NRM) has come to replace the more provocative term 'cult, ' however this shift of scholarly language has not resulted in a softening of public perception towards those in religious groups perceived as 'weird'. This perception leaves a distinct mark on the identities of children raised in these communities.Children from alternative and controversial religions comprise a unique subculture.. The experience of growing up in a new religious movement has an important impact on a young person's cultural and spiritual identity. Drawing on and expanding Useem and Downie's model of 'third culture kids' (TCKs) the model of 'alternative religion kids' (ARKs) is developed. It is proposed that ARKs are a subculture in their own right and share a sense of belonging and identity based on their experience of being religious 'others'. ARKs may be able to connect through a powerful, shared experience not paralleled with other peers.